AN INVESTIGATION ABOUT BIOCHEMICAL COMPONENTS OF MUSCLE AND SOME VISCERAL ORGANS IN Labeo rohita (Hamilton, 1822) CAUGHT FROM TWO DIFFERENT WETLANDS IN INDIA - BRRAICH, ONKAR SINGH; KAUR, NAVPREET (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The present study, it was aimed to examine and compare the total lipids, total proteins, carbohydrates, moisture and ash level in muscle and visceral organs of fish, Labeo rohita collected from two different wetlands in India seasonally. Simultaneously, the effect of industrial pollution on the health of fish has been scrutinized during the current research. The fish was collected during different seasons: rainy (July - September), autumn (September - November), winter (December - February), spring (March - mid April) and summer (Mid April - end June). In muscle, the higher average value of lipid (7.58±0.57%), protein (0.54±0.08%), carbohydrate (8.45±1.14%) and ash (3.62±0.20%) during all the seasons was reported in the control fish sample than test fish sample. Similarly, the higher mean value of lipid, protein and ash was found 8.58±0.46%, 0.91±0.23% and 2.84±0.11%, respectively, in control fish sample as compared to test fish sample. Furthermore, the maximum average value of lipid (7.76±0.36%), protein (0.37±0.07%) and carbohydrate (3.16±0.68%) was observed in the intestine of control fish sample than test fish sample. Biochemical parameters of muscle and visceral organs were decline significantly (P<0.05) in test fish samples than control fish. The decline in nutritional quality of the fish was caused by accumulation of industrial runoff because Harike wetland receives polluted water from the river Sutlej (Polluted water of Ludhiana city is being carried by the rivulet called Buddha Nullah and drained into the river Sutlej from left side) and another drain called Kala Sanghian carried polluted water from the Jalandhar district, Punjab and discharged into the river from right side. Protein concentration increased in the liver, muscle and intestine (autumn) of test fish samples during the present investigations. Increased production of total protein contents observed due to the acceleration of protein synthesis under the influence of toxicants in response to combat the stress situations. The increase or decrease in the values of carbohydrates, moisture and ash (%) in the muscle and visceral organs of test fish sample in contrast to control fish sample, proved the adverse impact of aquatic effluence on the health of fish. In conclusion, it is recommended that, possible measures should be taken to minimize the level of pollutants in this wetland.